Innovations in bio-inspired computing and applications : proceedings of the 6th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2015) held in Kochi, India during December 16-18, 2015 /: proceedings of the 6th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2015) held in Kochi, India during December 16-18, 2015. ([2015]) - Unknown
No abstract available